# If E=L then I=G+H, If E=S Then I=G-H. How???

1. ## If E=L then I=G+H, If E=S Then I=G-H. How???

Hi. Problems, problems....

I am trying to do a calculation whereby if Cell E=the Value "L" the Cell I=G-H.
Now, that part is Simple enough.

If cell E= "S" the Cell I should be G+H.

How ah???
Have tried IF and SUMIF Formula with no success. Maybe something simple but not for this brain at the moments.

Regards,
Martin

2. G'day and welcome to the forum,

Try this and cell references are all in row 2

Place this in cell I2

``Please Login or Register  to view this content.``

HTH

3. Lungfish, what happens when E is neither "L" nor "S"?

4. Lungfish,

Please read the Forum Rules about thread titles before starting your next thread.

#### Thread Information

##### Users Browsing this Thread

There are currently 1 users browsing this thread. (0 members and 1 guests)

#### Posting Permissions

• You may not post new threads
• You may not post replies
• You may not post attachments
• You may not edit your posts

Search Engine Friendly URLs by vBSEO 3.6.0 RC 1